New subclasses of analytic and M-fold symmetric bi-univalent functions defined by differential operator - Ramadan, Salma F.; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2019)
By using generalized differential operator, we introduce two new subclasses of analytic and m-fold symmetric bi-univalent functions in the open unit disk .U We also find coefficient estimates of 2a and 3a for these new subclasses.